2018
DOI: 10.1111/dom.13454
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, open‐label, multicentre, parallel‐controlled study comparing the efficacy and safety of biphasic insulin aspart 30 plus metformin with biphasic insulin aspart 30 monotherapy for type 2 diabetes patients inadequately controlled with oral antidiabetic drugs: The merit study

Abstract: BIAsp 30 plus metformin was non-inferior to BIAsp 30 in safely reducing HbA1c in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Metformin(Met) is the first-line drug for the treatment of T2DM and plays an anti-hyperglycemic role mainly by inhibiting liver glucose through AMPK-dependent or -independent pathways (11)(12)(13)(14). The Chinese MERIT study showed that premixed insulin combined with Met resulted in a greater reduction in HbA1c, less insulin consumption, less weight gain, a lower incidence of hypoglycemia, and lower cardiovascular risk than premixed insulin alone (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Metformin(Met) is the first-line drug for the treatment of T2DM and plays an anti-hyperglycemic role mainly by inhibiting liver glucose through AMPK-dependent or -independent pathways (11)(12)(13)(14). The Chinese MERIT study showed that premixed insulin combined with Met resulted in a greater reduction in HbA1c, less insulin consumption, less weight gain, a lower incidence of hypoglycemia, and lower cardiovascular risk than premixed insulin alone (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%